Deciphering the role of APOE in cerebral amyloid angiopathy: from genetic insights to therapeutic horizons - Hantian Hu; Siqi Wan; Yuetao Hu; Qi Wang; Hanyu Li; Nan Zhang (Annals of Medicine)
Cerebral amyloid angiopathy (CAA), characterized by the deposition of amyloid-β (Aβ) peptides in the walls of medium and small vessels of the brain and leptomeninges, is a major cause of lobar hemorrhage in elderly individuals. Among the genetic risk factors for CAA that continue to be recognized, the apolipoprotein E (APOE) gene is the most significant and prevalent, as its variants have been implicated in more than half of all patients with CAA. While the presence of the APOE ε4 allele markedly increases the risk of CAA, the ε2 allele confers a protective effect relative to the common ε3 allele. These allelic variants encode three APOE isoforms that differ at two amino acid positions. The primary physiological role of APOE is to mediate lipid transport in the brain and periphery; however, it has also been shown to be involved in a wide array of biological functions, particularly those involving Aβ, in which it plays a known role in processing, production, aggregation, and clearance. The challenges posed by the reliance on postmortem histological analyses and the current absence of an effective intervention underscore the urgency for innovative APOE-targeted strategies for diagnosing CAA. This review not only deepens our understanding of the impact of APOE on the pathogenesis of CAA but can also help guide the exploration of targeted therapies, inspiring further research into the therapeutic potential of APOE.